The Macroeconomic Environment for Jobs in South Sudan : Jobs, Recovery, and Peacebuilding in Urban South Sudan - Technical Report II - Mawejje, Joseph (World Bank, Washington, DC, 2020)
This study assesses the macro-fiscal framework for jobs in South Sudan, working with the limited macro-fiscal data available on the fiscal years 2019 and 2020. The macroeconomic environment can hardly be more difficult for South Sudanese looking to make a living. For workers, the dramatic contraction of non-oil output since the beginning of the conflict reflected a loss of job activities and a breakdown in market demand. A 60-fold increase in prices since before the conflict poses a serious obstacle to job activities, while an overvalued exchange rate weakens incentives. The oil sector is a big part of the economy, and the budget is dependent on oil revenue - but with weak governance, too little spending goes toward investment in development. The public sector in employment is large and a source of patronage, but it has an important function as a source of demand for goods and services. The study is one of a set of four reports assessing different aspects of jobs in urban South Sudan in order to formulate policy for recovery.